2017
DOI: 10.1557/jmr.2017.55
|View full text |Cite
|
Sign up to set email alerts
|

The microstructure and corrosion resistance of biological Mg–Zn–Ca alloy processed by high-pressure torsion and subsequently annealing

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…For the homogenized microstructure, the corrosion product layer is loose which is easily formed in vicinity of grain boundaries. Generally, the high density of grain boundaries is associated with the change of the structure discontinuity between the Mg matrix and layer which is beneficial for the formation of dense product layer [50,62]. The precipitated networklike film on the surface of the AEBed samples has calcium phosphate compounds such as hydroxyapatite, which is formed due to the reaction of phosphate and calcium ions with hydroxide ions in the SBF solution.…”
Section: Biocorrosion Behaviormentioning
confidence: 99%
“…For the homogenized microstructure, the corrosion product layer is loose which is easily formed in vicinity of grain boundaries. Generally, the high density of grain boundaries is associated with the change of the structure discontinuity between the Mg matrix and layer which is beneficial for the formation of dense product layer [50,62]. The precipitated networklike film on the surface of the AEBed samples has calcium phosphate compounds such as hydroxyapatite, which is formed due to the reaction of phosphate and calcium ions with hydroxide ions in the SBF solution.…”
Section: Biocorrosion Behaviormentioning
confidence: 99%
“…Nie et al [9] demonstrated that ECAP-processed NC pure iron (Fe) exhibited higher corrosion resistance and improved hemocompatibility and cytocompatibility. Zhang et al [64] investigated the corrosion resistance of an NC Mg-2Zn-0.24Ca (wt.%) alloy processed by HPT and annealing and reported that the grain size, number of (0002) oriented grains, second phase, and surface stress of the alloy changed with the annealing temperature and time, and these factors affected the corrosion rate. The HPT-processed alloy showed the best corrosion resistance with the maximum polarization resistance and lowest hydrogen evolution rate when annealed at 210 • C for 30 min.…”
Section: Biodegradable Nc Metallic Materials For Biomedical Applicationsmentioning
confidence: 99%
“…Mg-Based Composites for Biomedical Applications DOI: http://dx.doi.org /10.5772/intechopen.95079 In the case of magnesium, unlike aluminum or steel, the oxide layer is crystalline. There is no epitaxy between the oxide layer and the matrix with the compact hexagonal mesh (HCP), leading to a high compressive stress of the layer [18]. One of the ways to reduce discontinuity and have less disorder between the oxide layer and the metal surface is to introduce a large fraction of grain outlines per unit area [19].…”
Section: Mg Corrosionmentioning
confidence: 99%
“…However, it is known that HPT processing leads to a preferential orientation of the grains, of the magnesium alloy, in (0002) or basal plane. Since the basal plane is more stable than other non-oriented planes or grains, thus the increase in oriented grains (0002) increases corrosion resistance [18].…”
Section: Severe Plastic Deformationmentioning
confidence: 99%